PEMANFAATAN TEKNOLOGI OLEH GENERASI MILENIAL DI DESA LAUT DENDANG - Ahmad Faudi; Afrida Juliani; Abyena Hafza; Kartika Suci Ramadhani; Muhammad Fiqri Alwi; Putri Rizky; Raya Marcela; Sindy Adella; Siti Amalia Daulay; Yunizar Ritonga; Zahra Azzura Jaffa; Fadillah Putri Adeana (Educandumedia: Jurnal Ilmu pendidikan dan kependidikan, 2022)
The purpose of this study was to determine the role and government of the village towards the Millennial Generation in Laut Dendang Village. The method used in this study is a qualitative method with data collection techniques in this study using the methods of observation, interviews, and documentation. This is in accordance with the research objective to analyze the role of the village government of Laut Dendang towards the millennial generation. Based on the results of the study, it can be concluded that the role of the Laut Dendang Village Government towards the Millennial Generation in the village is to be able to manage public finances, mobilize community participation and the younger generation in the implementation of development, mobilize community participation and the younger generation in creating public order and security, and follow involve the younger generation in empowerment. Therefore, the village government includes the role of the millennial generation in the development of various tours in Laut Dendang Village, with the aim that the millennial generation can learn to manage and even improve tourism so that it develops more rapidly.